2023
DOI: 10.3389/fpubh.2023.1122418
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy among adults in Hawassa City Administration, Sidama Region, Ethiopia: A community-based study

Abstract: ObjectiveThe COVID-19 vaccine is one of the key measures to control the disease. However, some people are hesitant to take the vaccine. The objective of this study was to assess COVID-19 vaccine hesitancy and associated factors among adults in Hawassa City Administration, South Ethiopia.MethodFrom March 1 to 30, 2022, we conducted a community-based cross-sectional study among randomly selected 622 adults in Hawassa City Administration. A multi-stage sampling technique was used to recruit the study participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“… 34 , 35 This finding was smaller than that of a cross-sectional study of diabetic patients at Woldia Comprehensive Specialized Hospital, northern Ethiopia (82.6%) and the community-based study conducted at Hawassa City about COVID-19 vaccine acceptance (73.5%). 36 , 37 This difference might be due to the differences in the health status of the study population. This result is equivalent to that of studies conducted in the Gurage zone of Ethiopia (62.6%), a population-based anonymous online survey in Ethiopia (64.9%), a study conducted on healthcare workers in northeastern Ethiopia (64.0%), a study conducted at Wolkite University among medical and health science students with COVID-19 vaccine hesitancy (58.8%), a study conducted among Adult clients at public hospitals in Eastern Ethiopia using the HBM approach (54.6%), and two separate systematic and meta-analysis studies that pooled the prevalence of vaccine acceptance in Ethiopia (51.2% and 57.8%).…”
Section: Discussionmentioning
confidence: 98%
“… 34 , 35 This finding was smaller than that of a cross-sectional study of diabetic patients at Woldia Comprehensive Specialized Hospital, northern Ethiopia (82.6%) and the community-based study conducted at Hawassa City about COVID-19 vaccine acceptance (73.5%). 36 , 37 This difference might be due to the differences in the health status of the study population. This result is equivalent to that of studies conducted in the Gurage zone of Ethiopia (62.6%), a population-based anonymous online survey in Ethiopia (64.9%), a study conducted on healthcare workers in northeastern Ethiopia (64.0%), a study conducted at Wolkite University among medical and health science students with COVID-19 vaccine hesitancy (58.8%), a study conducted among Adult clients at public hospitals in Eastern Ethiopia using the HBM approach (54.6%), and two separate systematic and meta-analysis studies that pooled the prevalence of vaccine acceptance in Ethiopia (51.2% and 57.8%).…”
Section: Discussionmentioning
confidence: 98%
“…Having received vaccinations may be especially important in the urban context where individuals are frequently coming into contact with each other ( 89 ). This may be exacerbated by studies that have shown a high degree of vaccine hesitancy among Ethiopians ( 90 , 91 ), since low levels of vaccination allow for a greater prevalence of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore vital that health care services make sure any misconceptions are discussed with this high-risk population. The perceived risk to others was also a reason that was mentioned in some studies, this was demonstrated through vaccine enabling factors such as wanting to protect family and having a sense of community [8,36]. Highlighting the risk of transmitting the virus to more vulnerable populations may serve as a unique approach in public health messaging for those populations who may believe they are at low risk.…”
Section: Covid Risk Perceptionmentioning
confidence: 99%
“…Various studies considered the effect of religiosity; however, the results were varied. Some studies demonstrated that belief in religions (Catholicism, Buddhism, Islam) were barriers to vaccination, but other studies found that passivity towards religious practices was also a barrier [11,32,33,36]. Various cultural practices and norms were also identified as factors.…”
Section: Cultural Factorsmentioning
confidence: 99%
See 1 more Smart Citation